Management of Autoimmune Status Epilepticus - Kirmani, Batool F.; Barr, Donald; Robinson, Diana Mungall; Pranske, Zachary; Fonkem, Ekokobe; Benge, Jared; Huang, Jason H.; Ling, Geoffrey (Frontiers in Neurology, 2018)
Status epilepticus is a neurological emergency with increased morbidity and mortality. Urgent diagnosis and treatment are crucial to prevent irreversible brain damage. In this mini review, we will discuss the recent advances in the diagnosis and treatment of autoimmune status epilepticus (ASE), a rare form of the disorder encountered in the intensive care unit. ASE can be refractory to anticonvulsant therapy and the symptoms include subacute onset of short-term memory loss with rapidly progressive encephalopathy, psychiatric symptoms with unexplained new-onset seizures, imaging findings, CSF pleocytosis, and availability of antibody testing makes an earlier diagnosis of ASE possible. Neuroimmunomodulatory therapies are the mainstay in the treatment of ASE. The goal is to maximize the effectiveness of anticonvulsant agents and find an optimal combination of therapies while undergoing immunomodulatory therapy to reduce morbidity and mortality.